Circulating tumor cells as promising novel biomarkers in solid cancers*. (June 2014) - Lianidou, Evi S.; Strati, Areti; Markou, Athina
Abstract The presence of circulating tumor cells (CTCs) in peripheral blood can serve as a "liquid biopsy" approach and has thus emerged lately as one of the hottest fields in cancer research. CTCs can be isolated from blood in a non-invasive approach, and can be used to follow patients over time since these cells can provide significant information for a better understanding of tumor biology and tumor cell dissemination. CTC molecular characterization offers the unique potential to better understand the biology of metastasis and resistance to established therapies, and analysis of these cells presents a promising field for both advanced and early-stage patients. CTC detection, enumeration, and molecular characterization are very challenging since CTCs are rare, and the amount of available sample is very limited. Since detection of CTCs has been shown to be of considerable utility in the clinical management of patients with solid cancers, various analytical systems for their isolation and detection have been developed. New areas of research are directed towards developing novel assays for single-CTC isolation and molecular characterization. The clinical significance of CTCs has been evaluated in many types of solid cancers, and the CTC enumeration test in metastatic breast, colorectal, and prostate cancer was cleared by the FDA almost a decade ago. This review is mainly focused on the clinical potential of CTCs as novel biomarkers in 10 different types of solid cancers: breast, ovarian, prostate, lung, colorectal, hepatocellular carcinoma, pancreatic, head and neck, bladder cancer and melanoma.